Reconstruction of an AgPd nanoalloy with oxidation for formate oxidation electrocatalysis. Issue 26 (22nd June 2022) - Guo, Longfei; Jin, Tao; Tang, Quan; Wang, Junpeng; Pan, Bowei; Wang, Qiao; Li, Zhen; Wang, Chongyang; Liu, Jiawang; Chen, Fuyi
Abstract : AgPd–Ag2 O and AgPd–AgF heterointerfaces are prepared through reconstruction and designed by using "2D materials on metal" heterostructure models to illustrate their impact mechanism on electrocatalytic activity toward the formate oxidation reaction. Abstract : The emergence of heterointerfaces with two-dimensional oxide films grown on metal substrates has opened up a completely new opportunity for the development of energy conversion catalysts. However, mechanistic understanding for their enhancement in catalytic activity and guidance to precisely control their catalytic performance are still lacking. Herein, AgPd–Ag2 O and AgPd–AgF heterointerfaces are prepared through self-limiting reconstruction to illustrate their impact mechanism on catalytic performance toward the formate oxidation reaction (FOR). Especially, the AgPd–AgF interface exhibits optimal FOR catalytic performance, and its mass activity and retained activity after chronoamperometry are 1.96 and 2.97 times higher than those of AgPd. Ab initio molecular dynamics simulations confirm the formation of AgO x and AgF x adlayers upon the adsorption of O and F atoms. The limiting potentials for the oxidation of formate at the AgPd–AgF interface and on AgPd are 0.40 and 0.54 eV, while the energy barriers are 0.78 and 0.83 eV, respectively, indicating more favorable FOR thermodynamics and kinetics at the AgPd–AgF interface than on clean AgPd. Besides, the limiting potential of AgPd, AgF and AgPd–AgF with a tensile strain of 3% is decreased by 0.06, 0.27 and 0.13 eV compared with those without strain, revealing the promoting effect of reconstruction-induced tensile strain on FOR electrocatalysis. These findings should provide a universal guideline for engineering metal–oxide interfaces with atomic precision and designing high-performance catalysts with dynamic surface reconstruction.